Reflections on the COVID-19 mortality among the Black population and racial inequality in Brazil - Dantas, Marianny Nayara Paiva; Silva, Mercês de Fátima dos Santos; Barbosa, Isabelle Ribeiro (Saúde e Sociedade, 2022)
This literature critical analysis reflects on the social, political, and historical background responsible for racial discrepancies in hospital mortality by COVID-19 among the Brazilian population. During the pandemic, the COVID-19 mortality among the Black population gained notoriety. Rather than an isolated fact, this finding has historical roots dating back to Brazil’s foundation and draws on structural racism, which reveals degrading living and health conditions experienced by the Black population before the pandemic. This situation of vulnerability affecting the Black population is a recurring scenario that is treated with the neglect inherent to structural racism. COVID-19 mortality portrays one way in which racism impacts and reproduces itself in the life and death of Black people.